Mapeamento térmico facial em bugio-preto (Alouatta caraya) - Costa, André Luiz Mota da [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The black-and-gold howler monkey (Alouatta caraya) inhabits several regions in Brazil, Argentina, Paraguay and Bolivia and the conservation of the species has been threatened by deforestation, construction of roads and dams, hunting and outbreaks of wild yellow fever. The aim of this study was to use infrared thermography as a tool for mapping the facial temperature of black-and-gold howler monkeys, with the purpose of standardizing parameters that serve for the remote diagnosis of febrile processes present in infectious diseases; without the need for restraint, minimizing stress and prioritizing animal welfare. Were evaluated 153 images of a group of four healthy individuals (2 males and 2 females) kept under human care at the Sorocaba Zoo, SP, Brazil. The images were recorded by the FLIR T460 thermograph, during the period of one year, covering all seasons of the year and in the morning and afternoon periods, to cover all the climatic variables of the city where the zoo is located. Eye and face temperatures were evaluated. The results showed that there was a statistically significant difference in thermographic measurements between the eyes and the face (Student’s t test, P<0.05) for all seasons evaluated. A significant difference was also found between the seasons of the year, both for eye (P=0,014) and facial temperature (P<0,001). Mean values and standard deviations for facial and ocular temperature were respectively: 33.0 oC (2.1) and 36.5 oC (1.9) in the summer; 31.5 oC (4.5) and 35.3 oC (3.6) in the autumn; 30.0 oC (4.3) and 35.6 oC (3.9) in the winter; 30.8 oC (2.9) and 35.5 oC (2.1) in the spring. The use of infrared thermography for facial mapping of black-and-gold howler monkeys was effective, making it possible to establish a reliable parameter for eye and facial temperature.
Facial thermal mapping in black-and-gold howler monkey (Alouatta caraya)
Keywords: Face; Infravermelho; Olhos; Primatas; Termografia; Bugio-preto